Pengaruh Modal Kerja Terhadap Net Profit Margin (NPM) Pada PT Nippon Indosari Corpindo, Tbk - Adwiah, Nurwahatun; Muniarty, Puji (YUME : Journal of Management, 2024)
This research aims to determine the effect of working capital on Net Profit Margin (NPM) at PT Nippon Indosari Corpindo, Tbk. The research method used is associative research with a quantitative approach. The sample for this research consists of financial statements, balance sheet, profit and loss, current activities, current forestry, net profit and sales for 14 years from the 2008-2022 period. The research sampling was purposive sampling. With research data collection techniques using documentation and literature study. Data analysis techniques are simple linear regression, simple correlation coefficient, determination test, and t test. The research results show that there is no significant influence between working capital and Net Profit Margin (NPM) at PT Nippon Indosari Corpindo, Tbk. Keywords: Working capital, Net Profit Margin (NPM)